PERAN STRATEGIS MUHAMMADIYAH DALAM TRANSFORMASI ILMU PENGETAHUAN DAN PENDIDIKAN DI INDONESIA - Selvia Dias Devitamalla; Abdul Kholid Achmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategic role of Muhammadiyah in the transformation of science and education in Indonesia. This research used a qualitative approach with a library research method. The data were obtained from various literature sources such as scientific journals, books, articles, and documents related to the research topic. The results showed that Muhammadiyah has a significant contribution to the development of education in Indonesia through the establishment of educational institutions, the integration of science and Islamic values, and educational innovations that adapt to the development of the times. In addition, Muhammadiyah also plays a role in improving access and equity in education for communities in various regions. Based on the findings, it can be concluded that Muhammadiyah has a strategic role as an agent of change in the transformation of education in Indonesia. Through the concept of progressive Islam and renewal (tajdid), Muhammadiyah has succeeded in creating an educational system that is modern, adaptive, and still based on Islamic values.